Cannabinoid receptor-2 attenuates neuroinflammation by promoting autophagy-mediated degradation of the NLRP3 inflammasome post spinal cord injury - Jiang, Fan; Xia, Mingjie; Zhang, Yanan; Chang, Jie; Cao, Jiang; Zhang, Zhongkai; Qian, Zhanyang; Yang, Lei (Frontiers in Immunology, 2022)
Background: Neuroinflammation following spinal cord injury (SCI) results in prolonged damage of neurological histology and deteriorative dysfunction. Microglia polarization plays a vital role in regulation of neuroinflammation but such intricate mechanism regulated by various biological molecules was being explored. Endocannabinoid receptor subtype 2 (CB2R) was reported to ameliorate neurodegeneration attributed to its property of immunomodulation; however, its underlying machinery in the context of SCI remains unclear. Methods: A lipopolysaccharide (LPS)-induced microglia inflammation model and a mouse SCI model were employed to investigate the role of CB2R in regulating microglia polarization against neuroinflammation excess. Inflammatory and autophagy levels were measured using WB, immunofluorescence and ELISA assays, neuro-histology were visualized by HE, LFB and Nissl staining, ethology was assessed by BMS, footprint assay and LSS. Results: Our results showed that CB2R promoted M2 differentiation along with increased IL-10 expression, inhibited M1 differentiation with decreased expression of IL-1β and IL-6 targeting microglia. CB2R activation also increased ubiqutilation of NLRP3 inflammasome along with interaction with the autophagy-related proteins (p62 and LC3B). Treatment with CB2R activator JWH-133 reduced loss of myelin, apoptosis of neurons, and glia scarring, leading to an improved functional recovery of hindlimb locomotor, but all of which were reversed under treatment with CB2R inhibitor AM630. Conclusion: Taken together, the present study suggests that CB2R activation attenuates neuroinflammation targeting microglia polarization by promoting NLRP3 clearance, contributing to a protection of neuro-histology and an improvement of locomotor recovery post SCI.